Between a rock and a hard place - Lombard, PJ (Slope Stability 2020: Proceedings of the 2020 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2020)
Sharing in the closure and rehabilitation project challenges of a large open cast coal mine in South Africa from the initial stages to final closure can only be described as extremely rewarding. Watching draglines and dozers executing concurrent rehabilitation to the ultimate pleasure of witnessing rolling hills of grassland that are complimented by slopes covered in trees and shrubs through which contour berms flow and ebb guiding rainwater into energy dissipating gabion structures. Void filling with draglines and dozers enhances the project timelines, however, the compaction and settlement of the spoil material and the subsequent placing of topsoil challenges the final design levels due to the variation in time of material settlement dependent on the initial depth of the final voids. The overall design criteria for mine closure is premised on the swift removal of surface flows during rain events in order to limit water ingress into the spoil material and in achieving this, limiting the erosion potential of these flows to a minimum. The energy dissipating structures constructed as part of this design were fit for purpose, meaning that the structures will be stable and able to handle the design flow velocities on a continued basis without damage to the structures or uncontrolled erosion under, around or between the structures. Due to natural processes, erosion of the waterways (removal or deposition of sand/silt material) will take place between the structures. Fit for purpose will allow such natural processes to occur, provided it will be controlled and self-healing. Design and implementation challenges will reveal themselves in the performance of the structures, and this will be subject to certain limitations, which can influence the performance, sustainability and service life of the structures. Performance criteria are based on the ability for all water management structures to be able to withstand the 1:100 year 24-hour return period runoff event without major damage. The structures were designed and constructed in such a way that they will require low maintenance and are sustainable over the longer term. Low maintenance will mean that the structures will not require continued maintenance to keep them operating as intended. Maintenance will initially be higher than in subsequent years but limited to erosion control and vegetation maintenance. There should be a declining trend in maintenance requirements within the life expectancy of the materials used. Maintenance should not be more than what is envisaged during normal farming practices. The project will include a maintenance period of 12 months starting from the date of practical completion of the structures. Lessons learnt during this project will include design and construction improvements.
Keywords: energy dissipating gabion structures